Studies on crossability between elite types of cardamom (Elettaria cardamomum Maton) - PADMINI, M N VENUGOPAL, K (Journal of Spices and Aromatic Crops, 1999)
A 8 x 8 set of crosses including reciprocals were made between elite Malabar selections of cardamom (Elettaria cardamomum) namely, CCS-1 and RR-1 and six cardamom mosaic disease (katte) resistant lines (NKE-12, NKE-27, NKE-34, NK3,9, NKE-3 and NKE-19) to incorporate desirable characters in the hybrids. All the elite selections were compatible with each other; however, the degree of compatibility varied with the parents selected for hybridisation. The crossability was highest and significant in the cross NKE-19 x NKE-34 (92%) followed by NKE-12 x NKE-19 (77%) and NKE-12 x RR-1 (69%). The crossability in CCS-1 x RR-1, NKE-27 x CCS-1, NKE-12 x RR-1, NKE-9 x RR-1 and NKE-3 x RR-1 was high (>50%) indicating the scope for combining yield and disease resistance in these crosses.